The Characteristics of Effective Leadership on a Selected Sample of the Human Resources Sector in the Serbian Ministry of Interior - Janovac, Tatjana; Janovac, Tatjana; Virijević Jovanović, Saša; Zdravković, Jelena (NBP. Nauka, bezbednosti, policija, 2022)
Abstract One of the main goals of public sector reform in the Republic of Serbia is to develop professional capacity and create effective leadership. In general, effective leadership has a very significant role in public sector functioning. In addition, it is also important for the quality of public services that are delivered to citizens and other stakeholders. The fact that a small number of researchers have dealt with this issue was one of the motives that prompted the authors of this paper to approach the examination of internal factors that influence the development of effective leadership. Empirical research was conducted in the organizational units of the Sector for Human Resources of the Ministry of The Interior of The Republic of Serbia in July 2021 on a sample of 50 respondents. The aim of this research was to examine the attitudes of employees about the characteristics and behaviour of managers, which are internal factors that influence the process of developing effective leadership in the public sector. Statistical data processing identified the dominant characteristics, as well as the behavioural styles of managers. In addition, a correlation was found between leadership characteristics and behaviour. The statistical software in which the data processing and testing of the proposed hypotheses was performed was IBM SPSS version 23. Based on the results of empirical research, measures of effective leadership development during the period of public sector reform have been proposed. Keywords: employee attitudes, leadership characteristics, leadership styles, effective leadership, reform, public sector.